Ecosystem Monitoring on Leaves of Leaf Rust Disease of Maize (Zea mays L.) - Sopialena Sopialena; Suyadi Suyadi; Septri Alfian Noor (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Endemic leaf rust disease always occurs in almost all maize plantations in Indonesia. Furthermore, the development of this disease differs concurrently and is greatly influenced by the ecological conditions of maize cultivation. Therefore, this study fills the epidemiological gap of diseases that has not been conducted against the epidemiology of maize rust. This identifies the causes of leaf rust that attacked the maize plants in two locations, namely Bayur and Muang Dalam, Lempake, Samarinda, Indonesia. This study also analyzed the relationship or model between ecological factors of temperature, humidity, and soil fertility on the intensity of leaf rust and the infection rate of maize leaf rust. Measurement of disease intensity, the rate at which it developed, soil fertility and temperature and humidity of the area are conducted in this study. Meanwhile, soil fertility also influenced disease progression and the nutrient-poor soils in two sites cause leaf rust disease to develop well. The identification results showed that the cause of maize leaf rust was Puccinia sorghi Schw. Therefore, the temperature accompanied by the increased humidity is directly proportional to the development of the leaf rust.